The Influence of Expert Systems on Customer Satisfaction of Islamic Banks - Faizah Diah Hayuningtyas; Tiara Meilan Putri; Fatimah Nafisati Nugraheni; Ira Hapsari (UM Purwokerto Press, 2022)
This study discusses the Islamic banking industry, especially in Muslim countries, especially in Indonesia in order to improve the quality of Islamic banks by using an expert system. The use of expert systems in Islamic banks is a new thing so that it can be an innovation and a positive impact on the quality of Islamic banks. The development of Islamic banks is increasing along with the community's need for products, systems and services from Islamic banks, especially expert systems. An expert system is an information system from the knowledge of an expert that is used to assist non-experts in a particular field. Expert systems that can be used in Islamic banking such as the Decision Support System (DSS). Expert systems are useful for making decisions accurately and quickly compared to conventional systems. Expert systems in Islamic banking are new and have not been implemented. This refers to several conventional banks that use expert systems in their operations. The method used in this study is a quantitative approach and descriptive method with data collection techniques and data analysis techniques. The use of expert systems in banking greatly affects the level of efficiency of the information systems used, such as supporting decision-making to improve information systems in Islamic banks. Therefore, the use of expert systems in Islamic banking needs to be developed to improve the quality of transactions and reduce the error rate in the existing information systems in Islamic banking.